Effects of charging, strain, and doping on the interaction between H2 and nitrogen-rich Penta-CN2 sheet. (19th September 2022) - Ma, Li-Juan; Gao, Sheng-Qi; Jia, Jian-Feng; Wu, Hai-Shun
Abstract: The development of advanced materials for the safety and efficiency of hydrogen storage media is necessary. We computationally explored the hydrogen storage properties of penta-CN2 sheet. The hydrogen adsorption properties of neutral, negatively charged, externally strained, and metal-doped penta-CN2 sheets were investigated in detail. Here, for the first time, the effect of the strain of two-dimensional nonmetallic materials on hydrogen adsorption is investigated. We found that the hydrogen binding energy increases to −0.20 eV and achieves storage capacities up to 9.00 wt % on the negatively charged substrate, and to −0.14 eV at 18% stretching. Moreover, metal doping causes hydrogen adsorption energy to increase to −0.25–0.82 eV. The hydrogen storage capacity of Li-doped defective CN2 sheet is up to 10.90 wt%. Our study may provide new insights into the search for advanced materials for reversible hydrogen storage. Graphical abstract: The adsorption of H2 on penta-CN2 sheetcan be intensely enhanced under the action of negatively charging, external strain and metal doping. Image 1 Highlights: Hydrogen storage properties of penta-CN2 sheet is explored. Strain on hydrogen adsorption is investigated for the first time. H2 binding energy of the CN2 sheet is increased to −0.20 eV by negatively charging. The 18% strain increases the H2 binding energy of the CN2 sheet to −0.14 eV. The hydrogen storage capacity of Li-doped defective CN2 sheet is up to 10.90 wt%.